Neck dissection for head and neck malignancies: A Malaysian 13 years review (Bangladesh Journal of Medical Science, 2017)
Introduction and Objective: Neck dissection (ND) is a surgical procedure performed in treating head and neck cancer patients with cervical neck metastasis. The aim of neck dissection is to achieveloco-regional control thus optimizing the cancers cure rate. Various complications may potentially occur following this surgery. The main objective of this study is to evaluate the incidence of complications following neck dissection.Materials & Methods: This is a 13 years retrospective descriptive case notes analysis conducted in UKMMC (University Kebangsaan Malaysia Medical Centre), a tertiary centre in Malaysia. Neck dissection surgeries that were performed between January 2000tillDecember 2012 were recruited for data analyses.Results: A total of 233 neck dissections were performed in our centre over 13 years period from January 2000 until December 2012. Of these, 27 cases were excluded due to unavailability of data and therefore a total of 206 cases were recruited for data analyses.The types of neck dissection performed include Extended Radical ND (n=7), Radical ND (n=40), Modified Radical ND (n=88) and Selective ND (n=71). Majority of neck dissection was performed for malignant oral cavity tumours (47.1%). Out of 206 cases, 57 (27.7%) developed wound complications, 48 (23.3%) cases had nerve complications with marginal mandibular nerve was most commonly injured (13%) and 20 (9.7%) cases had vascular and lymphatic complications mainly involving the thoracic duct (5.3%). The incidence of residual or recurrent neck disease was observed in 41 cases (20%). Pre-operative clinical assesment of cervical neck node metastatic status has a high sensivity of 89.7% but low specificity of 47.5%.Conclusion: Various complications may potentially occur following neck dissection. Awareness of these possible complications could minimize the incidence of complication following this surgery. This current study observed a strong association between the type of neck dissection performed with the incidence of wound, nerve and vascularcomplications following neck dissection surgery.Bangladesh Journal of Medical Science Vol.16(3) 2017 p.384-396